Extensiveness of Teachers' Competence in Using Table of Specifications in Constructing Formative Assessment Test Items in Public Secondary Schools in Hanang District, Tanzania - Simon, Emanueli; Chidyau, Dr. Adam J.; Mandila, Dr. Timothy (International Journal of Scientific Research and Management (IJSRM), 2024)
The study examined teachers' competence in using tables of specifications in constructing formative assessment items in public secondary schools in Hanang district, Tanzania. Using Bloom's Taxonomy, a mixed-methods approach was employed, with 119 participants selected from 712 individuals, including teachers, heads of schools, academic masters/mistresses, and district school quality assurers. The study used questionnaires, interview guides, interview schedules and document analysis guides for data collection. Research experts assessed content and face validity for quantitative instruments, while qualitative instruments were validated through peer debriefing and triangulation. Data was presented in tables and analyzed using descriptive statistics and thematic analysis. The study revealed that public secondary school teachers vary in their competence of using the table of specifications when designing formative assessment test items. Moderately proficient teachers adhere to all procedures, while others struggle with determining question numbers and distribution. Based on the findings, the study concluded that teachers who are teaching students in public secondary schools were inadequately utilizing the table of specifications when designing formative assessment test items in public secondary schools. The study suggests that the government should prioritize professional development training to improve teachers' competencies in setting formative assessment test items, enhancing student learning outcomes.